Optimal force-velocity profile in ballistic movements--altius: citius or fortius? - Samozino, P.; Rejc, E.; Di Prampero, P. E.; Belli, A.; Morin, J.-B. (Medicine & Science in Sports & Exercise, 2012)
Purpose: The study's purpose was to determine the respective influences of the maximal power (Pmax) and the force-velocity (F-v) mechanical profile of the lower limb neuromuscular system on performance in ballistic movements.